Computational Science and High Performance Computing IV The 4th Russian-German Advanced Research Workshop, Freiburg, Germany, October 12 to 16, 2009 - Krause, Egon; Shokin, Yurii; Resch, Michael M.; Kröner, Dietmar; Shokina, Nina (Notes on Numerical Fluid Mechanics and Multidisciplinary Design, 2011)
This volume contains 27 contributions to the Forth Russian-German Advanced Research Workshop on Computational Science and High Performance Computing presented in October 2009 in Freiburg, Germany. The workshop was organized jointly by the High Performance Computing Center Stuttgart (HLRS), the Institute of Computational Technologies of the Siberian Branch of the Russian Academy of Sciences (ICT SB RAS) and the Section of Applied Mathematics of the University of Freiburg (IAM Freiburg) The contributions range from computer science, mathematics and high performance computing to applications in mechanical and aerospace engineering. They show a wealth of theoretical work and simulation experience with a potential of bringing together theoretical mathematical modelling and usage of high performance computing systems presenting the state of the art of computational technologies.